2021
DOI: 10.1002/ejlt.202000332
|View full text |Cite
|
Sign up to set email alerts
|

Pequi Oil, a MUFA/Carotenoid‐Rich Oil, Exhibited Protective Effects against DSS‐Induced Ulcerative Colitis in Mice

Abstract: Inflammatory bowel diseases (IBD) affect the gastrointestinal tract, and the imbalance of intestinal immune homeostasis can trigger them. Pequi oil (PO), a monounsaturated (MUFA) and carotenoid-rich food with nutraceutical potential, could help reshape the intestinal immune response, ameliorating IBD outcomes. This study investigates the effects of a 28 days intake of PO on elements of the intestinal immune response of mice with DSS-induced ulcerative colitis (disease activity index, colonic damage, inflammato… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(16 citation statements)
references
References 48 publications
0
16
0
Order By: Relevance
“…The pequi oil used in these studies was primarily extracted through solvent methods ( n = 4) [ 13 , 15 , 16 , 20 ], boiling ( n = 1) [ 6 ], cold-pressed/centrifugation ( n = 4) [ 6 , 14 , 17 , 19 ], and in two cases, the extraction method was not specified [ 12 , 18 ]. Additionally, some studies assessed the oil’s characteristics by analyzing the lipid profile ( n = 9) and other metabolites ( n = 7).…”
Section: Resultsmentioning
confidence: 99%
“…The pequi oil used in these studies was primarily extracted through solvent methods ( n = 4) [ 13 , 15 , 16 , 20 ], boiling ( n = 1) [ 6 ], cold-pressed/centrifugation ( n = 4) [ 6 , 14 , 17 , 19 ], and in two cases, the extraction method was not specified [ 12 , 18 ]. Additionally, some studies assessed the oil’s characteristics by analyzing the lipid profile ( n = 9) and other metabolites ( n = 7).…”
Section: Resultsmentioning
confidence: 99%
“…Ribeiro et al [45] described that β-carotene is the primary carotenoid in pequi oil, corresponding to 50% of its composition. Moreno et al [58] found more carotenoids in pequi pulp oil, nearly four times (549.84 µg of β-carotene/g of pequi oil) that found in pequi pulp (137.6 µg of β-carotene/g of pulp). Extractions performed at low temperatures favored obtaining an enriched β-carotene oil fraction due to the thermosensitivity of the pigment.…”
Section: Carotenoidsmentioning
confidence: 90%
“…The carrageenan-induced edema in vivo assay is traditionally used for screening and development of new compounds, and it is one of the most popular tests used due to its high sensitivity and reproducibility for anti-inflammatory and analgesic drugs [ 20 , 36 ]. Fixed natural oils, such as pequi oil, have demonstrated potential anti-inflammatory, anti-edema, and antinociceptive activities [ 5 , 6 , 14 , 15 , 16 , 17 ]. Junior and co-workers [ 5 ] have described significant anti-inflammatory and antinociceptive effects of free pequi oil with a single oral administration with doses of 700 mg/kg and 1000 mg/kg respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have described the anti-inflammatory and antinociceptive activities of free pequi oil in different models [ 5 , 6 , 14 , 15 , 16 , 17 ]. Interestingly, to the best of our knowledge, only one study has evaluated the anti-inflammatory effects of a nanostructured pequi oil in an in vivo model [ 6 ].…”
Section: Introductionmentioning
confidence: 99%